2020
DOI: 10.1177/1098300719900318
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of the Effects of BEST in CLASS–Elementary on Outcomes of Elementary Students With Problem Behavior

Abstract: Student problem behaviors in early elementary school are associated with fewer learning opportunities, poor relationships with teachers, and academic and behavioral problems, including increased risk of emotional/behavioral disorders (EBDs). This study examined the effect of BEST in CLASS–Elementary (BEST in CLASS-E), a Tier 2 intervention delivered by teachers, on student problem behavior, academic achievement, teacher–student relationships, and classroom quality using a randomized controlled trial design. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…In addition, as reported in Sutherland et al (2020), the classroom-level adversity scores in the classrooms in this study were high (means of 3.00 and 3.01 in BEST in CLASS-E and BAU classrooms, respectively, on a 4-point scale), indicating that students in these classrooms faced high levels of stress consistent with ecological challenges (i.e., poverty, toxic stress, and social and academic difficulties). Furthermore, there was a lack of Tier 1 practices in place that also may have impacted study results.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…In addition, as reported in Sutherland et al (2020), the classroom-level adversity scores in the classrooms in this study were high (means of 3.00 and 3.01 in BEST in CLASS-E and BAU classrooms, respectively, on a 4-point scale), indicating that students in these classrooms faced high levels of stress consistent with ecological challenges (i.e., poverty, toxic stress, and social and academic difficulties). Furthermore, there was a lack of Tier 1 practices in place that also may have impacted study results.…”
Section: Discussionsupporting
confidence: 70%
“…The purpose of this study was to examine the effects of BEST in CLASS-E, a Tier-2 intervention that provides professional development, including practice-based coaching to increase teachers' delivery of evidence-based practices with higher quantity and quality to young students with and at risk for EBD, on a number of teacher outcomes associated with positive student outcomes. Previous research on BEST in CLASS-E (Sutherland et al, 2020) indicates its promise at reducing students' problem behavior and increasing teacher-student closeness, while research on the preschool version of BEST in CLASS has found positive effects for both child (Conroy et al, 2018;Sutherland et al, 2018a) and teacher (Conroy, Sutherland et al, 2019) outcomes. In this study, teachers in the BEST in CLASS-E condition delivered practices with greater adherence and competence from pretest to posttest, whereas teachers in the BAU condition had decreases on both of these treatment integrity dimensions; meanwhile, student responsiveness increased in the BEST in CLASS-condition but decreased over time in the BAU condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And it is well documented that classroom management strategies can positively and preventatively support appropriate behavior, influence teacher-child relationships, and promote positive academic and social outcomes (Chow & Gilmour, 2016;Maggin et al, 2017;Moore et al, 2017;Simonsen et al, 2008). Much of the empirical research supporting the benefits of classroom management practices provide teachers with ample time for establishing classroom management practices, some with intensive coaching and feedback (Kamps et al, 2015;Sutherland et al, 2020). This is important because coaching can lead to increases in classroom management efficacy, which is associated with children's literacy growth (Varghese et al, 2016).…”
Section: Ecological-transactional Frameworkmentioning
confidence: 99%